Helicobacter pylori impairs murine dendritic cell responses to infection. - Ya-Hui Wang; Jean-Pierre Gorvel; Yen-Ting Chu; Jiunn-Jong Wu; Huan-Yao Lei (PLoS ONE, 2010)
BACKGROUND: Helicobacter pylori, a human pathogen associated with chronic gastritis, peptic ulcer and gastric malignancies, is generally viewed as an extracellular microorganism. Here, we show that H. pylori replicates in murine bone marrow derived-dendritic cells (BMDCs) within autophagosomes. METHODOLOGY/PRINCIPAL FINDINGS: A 10-fold increase of CFU is found between 2 h and 6 h p.i. in H. pylori-infected BMDCs. Autophagy is induced around the bacterium and participates at late time points of infection for the clearance of intracellular H. pylori. As a consequence of infection, LC3, LAMP1 and MHC class II molecules are retained within the H. pylori-containing vacuoles and export of MHC class II molecules to cell surface is blocked. However, formalin-fixed H. pylori still maintain this inhibitory activity in BMDC derived from wild type mice, but not in from either TLR4 or TLR2-deficient mice, suggesting the involvement of H. pylori-LPS in this process. TNF-alpha, IL-6 and IL-10 expression was also modulated upon infection showing a TLR2-specific dependent IL-10 secretion. No IL-12 was detected favoring the hypothesis of a down modulation of DC functions during H. pylori infection. Furthermore, antigen-specific T cells proliferation was also impaired upon infection. CONCLUSIONS/SIGNIFICANCE: H. pylori can infect and replicate in BMDCs and thereby affects DC-mediated immune responses. The implication of this new finding is discussed for the biological life cycle of H. pylori in the host.